Diversity of Reef Associated Fauna in Outer Gulf of Kachchh, Gujarat, North Eastern Arabian Sea, India - N. N. Katira; B. B. Nayak; A. K. Jaiswar; N. H. Joshi; Hitesh Kardani; Geetanjali Deshmukhe (Journal of Indian Fisheries Association, 2021)
Gulf of Kachchh is blessed with huge genetic diversity and unique ecosystems like a coral reef, mangroves, rocky beaches, sandy shore, and mudflats. The coral reef ecosystem is known to provide habitat for diverse flora and fauna and more species per unit area than any other ecosystem. The present study, on reef-associated faunal diversity in the outer gulf, is an initiative to know the state of the health of the coral reef ecosystem in the outer gulf area. During the study, 39 species of reef-associated fauna belonging to 35 genera and 30 families, were recorded from three selected sites of the outer Gulf of Kachchh region. The highest number of reef-associated fauna was recorded from Shivrajpur (29) followed by Okha (28) and Mithapur (23). The present study reveals the status of reef diversity among the three selected sites and will help for the conservation and development of precious reef ecosystems in the outer gulf.